Consistency and risk stratification performance of 4 society for cardiovascular angiography and interventions SHOCK stage definitions: A Retrospective Study - Becher, Tobias; Hahn, Leonie; Britsch, Markward; Muschko, Marc; Langer, Harald; Lindner, Simon; Helbing, Thomas; Hahn, Michael; Jabbour, Claude; Dürschmied, Daniel; Britsch, Simone (Journal of the American Heart Association, 2025)
Background - Cardiogenic shock (CS) is a critical condition associated with high mortality rates, making prompt diagnosis essential for timely interventions that may improve patient outcomes. The Society for Cardiovascular Angiography and Interventions (SCAI) SHOCK Stage Classification is a validated tool for assessing CS and predicting patient outcomes. Here, we evaluated how different parameter definitions affect SCAI stage adjudication, hypothesizing that variations may influence stage determination and the overall assessment of CS. - Methods - All patients diagnosed with CS or conditions leading to CS at the University Medical Center Mannheim, Germany, from January 2018 to June 2022 were included in the study. SCAI SHOCK stages were assigned retrospectively on the basis of 4 previously published studies. The distribution of SCAI SHOCK stages, outcomes, classification concordance, and predictive performance were assessed. - Results - From January 2018 to June 2022, we identified 1303 patients on the basis of International Classification of Diseases, Tenth Revision (ICD‐10) codes. Of these, 1281 patients (98.2%) were classified into SCAI SHOCK stages according to all 4 classification frameworks. While the assignment of SCAI SHOCK stages and associated mortality rates varied among the frameworks, Kendall's W indicated moderate to strong overall classification agreement (W=0.70). There was no significant difference in predictive performance for in‐hospital death. - Conclusions - Our study demonstrates a moderate to strong concordance and comparable prognostic performance across different SCAI SHOCK Stage Classification frameworks in evaluating patients with CS. Despite differences in stage assignments, all frameworks effectively stratified patients by clinical severity. Comparable stage assignment in retrospective studies requires further standardization of the SCAI SHOCK Stage Classification system.
Online veröffentlicht: 22. August 2025
Gesehen am 19.11.2025